A Longitudinal Study of Truant Youths' Involvement in Sexual Risk Behavior. Issue 2 (3rd March 2016) - Dembo, Richard; Briones-Robinson, Rhissa; Wareham, Jennifer; Winters, Ken C.; Ungaro, Rocío; Karas, Lora
ABSTRACT: Truant youths are likely to engage in a number of problem behaviors, including sexual risky behaviors. As part of a National Institute on Drug Abuse (NIDA)-funded, prospective intervention project, a sample of truant youths' sexual risk behavior was tracked over five time points. Analyses of the data was informed by four objectives: (a) determine if a growth model parameterization was consistent with the youths' sexual risk behavior, (b) assess the impact of a brief intervention (BI) targeting substance use on their sexual risk behavior over time, (c) identify any sexual risk behavior subgroups, and (d) identify any differential, longitudinal effects of the BI on the youths' sexual risk behavior. Results indicated the youths' sexual risk behavior reflected a linear growth model; no intervention effects were found on their sexual risk behavior over time; distinct sexual risk behavior subgroups were found; and no patterned intervention effects were found in regard to the sexual risk behavior subgroups. At the same time, there is a very serious need to provide effective sexual risk reduction intervention services to truant youths.